2015
DOI: 10.1152/ajpheart.00200.2015
|View full text |Cite
|
Sign up to set email alerts
|

Substance P induces cardioprotection in ischemia-reperfusion via activation of AKT

Abstract: Accumulating evidence indicates that substance P is cardioprotective following ischemia-reperfusion primarily due to its potent coronary vasodilator actions. However, an anti-apoptotic effect of substance P has been observed in tenocytes following ischemia, which involved activation of the AKT pathway. This suggests the possibility that substance P also provides cardioprotection via direct actions to activate AKT in myocardial cells. The purpose of this study was to test the hypothesis that substance P attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
1
15
0
Order By: Relevance
“…Chanoit et al reported that Akt mediated exogenous zinc-induced cardioprotection against reperfusion injury (45). The Akt pathway is also involved in the cardioprotection of substance P against ischemic/hypoxia-induced myocardial cell death (46). Moreover, the impaired activation of Akt has been shown to participate in diabetic cardiomyopathy (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Chanoit et al reported that Akt mediated exogenous zinc-induced cardioprotection against reperfusion injury (45). The Akt pathway is also involved in the cardioprotection of substance P against ischemic/hypoxia-induced myocardial cell death (46). Moreover, the impaired activation of Akt has been shown to participate in diabetic cardiomyopathy (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…However, isolated neonatal rat cardiomyocytes have been shown to possess NK1R and NK3R mRNAs, but not NK2R mRNA ( Church et al, 1996 ). Recently, the presence of NK1R on isolated adult cardiomyocytes has been shown in rat ( Jubair et al, 2015 ). Although our results and the results of other authors did not confirm the presence of NK1R in cardiomyocytes, data obtained by functional studies suggest a direct protective action of SP on cardiomyocytes by NK1R ( Jubair et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, accumulating evidence indicates that SP is cardioprotective due to its potent coronary vasodilator effects ( Chiao and Caldwell, 1995 ; Ustinova et al, 1995 ; Wang et al, 2011 ). Moreover, a recent study suggests that cardioprotective role of SP performed throughout its direct actions on cardiomyocytes ( Jubair et al, 2015 ). Therefore, the purpose of this study was to investigate the gene and protein expression of NK1R in all heart compartments of rats.…”
Section: Introductionmentioning
confidence: 99%
“…This further indicates that Ang II might activate the aforementioned downstream signaling pathway genes by acting on TGF-β1 and thereby promoting the activation of the genes related to collagen synthesis in CFBs. Other studies showed that the protective effect of the combined SP and NK1 receptors on injured myocardial cells in myocardial ischemia might be realized by AKT signaling pathways [27]. Therefore, SP can be an advantageous protection factor in myocardial fibrosis and play its role by way of downstream pathways when bound with SP receptors.…”
Section: Discussionmentioning
confidence: 99%